Regulating Land-Use Conversion for Sustainable Tourism: A Case Study of Lodtunduh Village, Ubud - Diah Utari Dewi, Nyoman; Trisna Juliantari Dewi, Desak Made; Ayu Putu Sri Widnyani, Ida; Tirka Widanti, Ni Putu (Indonesian Association for Public Administration (IAPA), 2024)
The phenomenon of land-use conversion in Lodtunduh Village, Ubud Subdistrict, is a direct result of rapid tourism development and the escalating land prices in the area. Despite the existence of customary regulations (awig-awig) aimed at managing the transformation of agricultural land into commercial spaces for tourism purposes, the enforcement of these regulations faces signiﬁcant challenges. This study aims to analyze the eﬀorts by the traditional village to support sustainable tourism through land-use control. Using a qualitative approach, data were collected through interviews, observations, and secondary sources. The ﬁndings reveal that land-use conversion in Lodtunduh is primarily driven by tourism expansion and housing demand. While these developments contribute positively to the local economy, they exert considerable negative eﬀects on the environment and agricultural sectors. The customary regulations imposed by the village through awig- awig have successfully curbed nearly 40% of land conversion activities. Active community participation in deliberations and oversight mechanisms has been instrumental in preserving the remaining agricultural land. However, economic pressures from the tourism industry, coupled with low public awareness of environmental issues, present critical challenges that demand heightened aMention.